2018
DOI: 10.1111/lam.13078
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of by-product from beverage industry through solid-state fermentation withCandida utilisandBacillus subtilis

Abstract: Significance and Impact of the Study: Yellow wine lees (YWL) are the main co-products in yellow wine industry with unbalanced amino acid (AA) profiles and are not well utilized. A strain combination of Candida utilis and Bacillus subtilis was employed to upgrade YWL. Contents of crude protein and peptides of YWL were greatly increased by microbial fermentation. Essential AAs of YWL were highly improved after the solid-state fermentation and no negative impact was observed in in vitro digestibility. Fermented Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
2
13
0
1
Order By: Relevance
“…The solid-state fermentation of YWL mix was conducted following the procedure established in the previous study (Yao et al 2018). The fermentation substrate consisted of YWL, wheat bran, cassava residue and glucose at a ratio of 400, 500, 50 and 50 g/kg, respectively.…”
Section: Production Of Fermented Yellow Wine Leesmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid-state fermentation of YWL mix was conducted following the procedure established in the previous study (Yao et al 2018). The fermentation substrate consisted of YWL, wheat bran, cassava residue and glucose at a ratio of 400, 500, 50 and 50 g/kg, respectively.…”
Section: Production Of Fermented Yellow Wine Leesmentioning
confidence: 99%
“…The quantity of the microorganisms was maintained at 10% (w/v) while the inoculum ratio of the two strains was 1:1 (v/v), and sterilised water was added to the solid medium maintaining a water-to-material ratio of 1:1 (v/w) and a pH value of 6.8-7.2. The medium was placed evenly on the tray with a single layer of sterilised gauze, covered and then placed in a constant temperature incubator (Yao et al 2018). All media were dried after being incubated at 30 C for 48 h.…”
Section: Production Of Fermented Yellow Wine Leesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dependendo da quantidade de calor que é formada nesse processo, pode ocorrer uma diminuição da produção da enzima dentro do reator, sendo este, um fator negativo. De acordo com Schmidell e Facciotti (2001) e Yao et al (2018) é importante que ocorra um controle desse calor no processo de fermentação solida, desta forma, é essencial que exista um mecanismo para dissipar ou diminuir a temperatura interna no reator. Neste trabalho, utilizou-se um sistema de agitação com uma pá mecânica, rotacionando dentro do reator, sendo esta agitação controlada pelo CLP.…”
Section: Influência Da Agitação No Meio De Fermentação E Produção Da unclassified
“…Studies have shown the beneficial effects of probiotics in improving the GM, and they can further promote human health, immunity and digestion (24,25) . It has been reported that B. subtilis can effectively regulate GM (26,27) . It was demonstrated that a higher dose of B. subtilis administration ameliorated dextrose sulfate sodium (DSS)-induced dysbiosis and gut inflammation by balancing beneficial and harmful bacteria and associated anti-and pro-inflammatory agents, therefore aiding intestinal mucosa recovery from DSS-induced injuries (28) .…”
mentioning
confidence: 99%